Human Dignity and Citizenship Right in the Eyes of Imam Khomeini (ra) - محسن پرواز (سپهر سیاست, 2016)
In a world where liberal-democratic thought as one of the discourses at issue in the world have made western thinkers regard it the only true way of administering people and set aside religion from the scene of politics in its entirety; they want to instil the belief that religion cannot manage human community. In the Islamic Iran, a religious government was formed based on Velayat-e-Faqih led by the sagaciously jurisprudent leader, Hazrat Imam Khomeini (ra) in such a way that the world people once observing this government learned that religion has something to say and it can lead human communities towards prosperity by recognizing psychological and mental needs. The most marked cases of citizenship rights in the eyes of Hazrat Imam Khomeini (ra) are right of freedom, right of security, right of having social justice and the other rights trace back to these three main elements. The fundamental origin of such rights are natural rights according to the Islamic universalism and Hazrat Imam Khomeini (ra) that emanate from divine credibility. In fact, citizenship rights that are divinely endowed to social mankind and nobody is authorized to deprive him of such endowed rights.